Navigation and Obstacle Detection for Visually Impaired Individuals Using RFID and Supersonic Sensor - M.Anto Bennet, Dr.; T Tharshini, V.; Vinothini, V.; Aaryani, M.; Soundarya, S.; Akshara, S. (International Journal of Engineering and Technology, 2018)
This work represents the implementation and architecture of a system that helps the visually impaired people (VIPs) to navigate to their desired location. The system is designed with RFID tag and voice communication along with obstacle avoidance for the purpose of guiding visually impaired people. The visually impaired people issues the command through a Braille keypad (supermarkets, medicals, hospitals and stores)    and receives the direction response by using a RFID tag as an audio message.  Supersonic sensor is used to detect an obstacle to avoid collision in their surroundings by sending an audio message. ZigBee protocol is also used to intimate the VIPs about the traffic signals in order to avoid accidents. With the advancement in voice communication it becomes easier to issue commands regarding directions to the visually impaired people. In future it can be implemented with GPS for long distance navigation.